Manejo agronómico del cultivo de albahaca (Ocimun basilicum L.) en el Ecuador - Montoya Montero, Jennifer Stefanya (2022)
In the present investigation on the agronomic management of basil cultivation (Ocimun basilicum L.). The basil plant prefers warm and temperate climates, it grows in temperatures that range between 15 and 25 0C, not reproducing in low temperatures. It is also an easy-to-produce crop, where housewives grow them indoors, on their terraces or in greenhouses. The conclusions determine that little information is presented concerning the agronomic management of basil cultivation in Ecuador, highlighting that the available information is not updated, therefore it is essential that the sowing of the cultivar be promoted to generate new publications, especially in our country. ; the crop is easy to produce, it can be done by farmers, like housewives; and the necessary tasks are required such as seedbed, transplant, sowing (in ample land or in pots, greenhouse), pruning, weed control, pests, diseases and harvest and it is considered as a food, medicinal and economically important seasoning plant for the soap industry, perfumery. It is also used as a repellent botanical insecticide for insects. however, it is necessary to promote the planting of basil as an alternative crop for farmers, without leaving aside their traditional cultivars; carry out field tests to obtain results that can be published and carry out training on planting the crop for housewives in rural areas through the program for linking with society.